Comparison of the clinical performance of the flexible laryngeal mask airway in pediatric patients under general anesthesia with or without a muscle relaxant: study protocol for a randomized controlled trial - Sung Hye Byun; Soo Jin Kim; Eugene Kim (Trials, 2019)
Abstract Background The insertion of a laryngeal mask airway (LMA) is difficult in children due to the unique features of their airways. Muscle relaxants have been reported to facilitate LMA insertion in adults; however, there is a lack of evidence supporting this in children. This trial is designed to assess the feasibility of LMA insertion with and without the use of muscle relaxants in pediatric patients under general anesthesia. Methods/design This is a prospective, double-blind, single-center, parallel-arm, non-inferiority, randomized controlled trial to be conducted with participants aged 2–7 years who are undergoing elective ophthalmic surgery under general anesthesia. Participants are randomly assigned to one of two groups based on whether muscle relaxants are used (MR group, n = 64) or not used (Saline group, n = 64) prior to LMA insertion. The primary outcome is the oropharyngeal leak pressure (OLP) at a fixed gas flow of 3 L/min. The secondary outcomes are intubation time for successful insertion, ease of insertion and mask bagging, intubation attempt for successful insertion, successful insertion rate on the first attempt, fiberoptic view of the LMA position, postoperative complications, and changes in hemodynamic and ventilatory parameters. Discussion We will compare the OLPs to determine whether the muscle relaxant provides better conditions for the manipulation of the LMA. This is the first randomized controlled trial to investigate whether muscle relaxants are beneficial to the clinical performance of LMA insertion in pediatric patients under general anesthesia. This trial will be a resource for improving the process and safety of pediatric LMA insertion under general anesthesia. Trial registration ClinicalTrials.gov, NCT03487003. Registered on 18 April 2018.